A robust UV–visible light‐driven SBA‐15‐PS/phthalhydrazide nanohybrid material with enhanced photocatalytic activity in the photodegradation of methyl orange. (18th May 2018) - Tayebee, R.; Mohammadzadeh Kakhki, R.; Audebert, P.; Amini, M. M.; Salehi, M.; Mahdizadeh Ghohe, N.; Mandanipour, V.; Karimipour, G.R.
Abstract : SBA‐15‐PS/phthalhydrazide (PHD) is presented as a new heterogeneous inorganic–organic nanohybrid photocatalyst with high stability, superior recyclability and remarkable performance in the degradation of methyl orange (MO). Distinctive parameters, including photocatalyst and dye concentrations, pH and degradation time, were assessed for MO degradation catalysed by SBA‐15‐PS/PHD. This new heterogeneous nanocatalyst was characterized using Fourier transform infrared and UV–visible spectroscopies, thermogravimetric analysis, scanning and transmission electron microscopies and elemental analysis. Photodegradation of MO of up to 92% under the optimum conditions (photocatalyst = 0.015 g, [MO] = 4 ppm, pH = 2) was accomplished in 25 min using SBA‐15‐PS/PHD. A preliminary kinetic investigation was performed, and pseudo‐first‐order kinetics with a high rate constant (0.068 min −1 ) was found for MO degradation. Additional results showed that the photodegradation of MO was increased in the presence of hole scavengers. Therefore a photoreduction mechanism for MO degradation is proposed. Abstract : SBA‐15‐PS/PHD is introduced as a new, efficient, stable and reusable inorganic–organic nanohybrid photocatalyst for the photodegradation/photoreduction of azo dye methyl orange.